Study of the Stone Age in the Republic of Armenia (Part 1 – Lower Palaeolithic) - Gasparyan, Boris; Adler, Daniel S.; Wilkinson, Keith N.; Nahapetyan, Samvel; Egeland, Charles P.; Glauberman, Philip J.; Malinsky-Buller, Ariel; Arakelyan, Dmitri; Arimura, Makoto; Dan, Roberto; et al. (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
The area encompassing the modern Republic of Armenia lies within the Armenian highlands and is situated at the very core of a dynamic corridor between Africa and Eurasia. As such, Armenia proves critical for understanding the initial stages of human settlement and the formation of ancient civilisations in the Near East and beyond. Stone Age artefacts have been known to exist within the territory of Armenia since the end of the 19th century, and they indicate that the area attracted a variety of Stone Age populations, from early hominids to early complex societies of the Chalcolithic. Presented work is the first attempt to summarise the results and achievements of the Stone Age archaeology in Armenia which is counting its history more than a century.